PENERAPAN ASUHAN KEPERAWATAN DENGAN INTERVENSI COGNITIVE BEHAVIORAL THERAPY (CBT) SEBAGAI UPAYA MENGURANGI PERILAKU MEROKOK PADA REMAJA DI RW 04 SUNGAI BAMBU - Indah Sari (2022)
Adolescence is a transition from children to adults. In adolescence the level of curiosity increases so that the teenager will dabble in something he has never done. Smoking is one of the behaviors that many teenagers do. Smoking behavior in adolescents should be reduced so as not to cause many diseases in the future. The purpose of this study was to address smoking behavior in adolescents through cognitive behavioral therapy (CBT) interventions. The administration of CBT therapy was given to two adolescents in RW 04 who had high smoking behavior. The implementation of CBT therapy is carried out as many as five meetings with a duration of 40-60 minutes for each meeting. The results of the implementation of CBT therapy showed that after CBT therapy, the smoking behavior score in two adolescents decreased. The first adolescent experienced a decrease in behavior score from a score of 72 (high behavior) to 56 (moderate behavior) and the second adolescent experienced a decrease in the score from 75 (high behavior) to 60 (moderate behavior). The two teenagers also had a change in the number of cigarettes consumed per day after doing CBT therapy, from 12 cigarettes per day to 7 cigarettes per day after doing CBT therapy, from 12 cigarettes per day to 7 cigarettes per day. Community nurses are expected to be able to use cognitive behavioral therapy in overcoming smoking behavior in adolescents.